1994
DOI: 10.1083/jcb.126.2.289
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in the higher-level chromatin organization of specific sequences revealed by in situ hybridization to nuclear halos.

Abstract: Abstract.A novel approach to study the higher level packaging of specific DNA sequences has been developed by coupling high-resolution fluorescence hybridization with biochemical fractionation to remove histones and distend DNA loops to form morphologically reproducible nuclear "halos y Results demonstrate consistent differences in the organization of specific sequences, and further suggest a relationship to functional activity. Pulse-incorporated bromodeoxyuridine representing nascent replicating DNA localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
1
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(129 citation statements)
references
References 70 publications
8
118
1
2
Order By: Relevance
“…Analysis of spatial positions of BCRs present in AML-1 and ETO genes by in situ hybridization of BCR probes with nuclear halos Visualization of specific DNA sequences on nuclear halos by hybridization opens the possibility of studying their partitioning between matrix-bound and looped-out DNA fractions (Balajee et al, 1996;Gerdes et al, 1994;Ratsch et al, 2002). In our recent experiments, this method was successfully used to study the partitioning of the human dystrophin gene into loop domains (Iarovaia et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of spatial positions of BCRs present in AML-1 and ETO genes by in situ hybridization of BCR probes with nuclear halos Visualization of specific DNA sequences on nuclear halos by hybridization opens the possibility of studying their partitioning between matrix-bound and looped-out DNA fractions (Balajee et al, 1996;Gerdes et al, 1994;Ratsch et al, 2002). In our recent experiments, this method was successfully used to study the partitioning of the human dystrophin gene into loop domains (Iarovaia et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear halos were prepared essentially as described (Gerdes et al, 1994;Cai and Kohwi-Shigematsu, 1999). In brief, cultured mouse spleen cells and transfected mouse cells were harvested; then immersed in 4°C CSK buffer containing 0.5% Triton X-100 for 10 minutes.…”
Section: Halo Preparationmentioning
confidence: 99%
“…Following histone extraction, these loops can be visualized as a DNA halo anchored to the densely stained nuclear matrix or chromosomal scaffold (Vogelstein et al, 1980;Gerdes et al, 1994;Bickmore and Oghene, 1996). As a basic unit, the loop is essential for DNA replication, transcription regulation and chromosomal packaging (Gasser and Laemmli, 1987;Berezney et al, 1995;Bode et al, 1995;Nickerson et al, 1995;Razin et al, 1995;Jackson, 1997;Stein et al, 1999;Sumer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Because young mice have transcriptional rates higher than those of adult mice (32), this chromatin may mostly be attached to the nuclear matrix, thus explaining absence of ECF formation in these nuclei, despite relatively low condensation of this chromatin in relation to that of the adult mice. Considering the hypothesis of Gerdes et al (52), the hepatocyte nuclei from old mice, which showed higher ECF formation compared to that of adults, could have a reduced number of DNA-nuclear matrix interactions, reflecting reduced gene activity and low metabolism.…”
Section: Chromatin Supraorganization and Extensibilitymentioning
confidence: 99%
“…In the present study, the absence of ECF formation in fixed hepatocyte nuclei of young mice could not be associated with chromatin condensation. Gerdes et al (52) stated that DNA sequences attached to the nuclear matrix (MARs), which are resistant to saline extraction, are located in regions where the DNA is being transcribed or replicated. Because young mice have transcriptional rates higher than those of adult mice (32), this chromatin may mostly be attached to the nuclear matrix, thus explaining absence of ECF formation in these nuclei, despite relatively low condensation of this chromatin in relation to that of the adult mice.…”
Section: Chromatin Supraorganization and Extensibilitymentioning
confidence: 99%